The impact of political skill towards organizational commitment: a case study on Petronas / Farah Amira Mohammad Zaidi - Mohammad Zaidi, Farah Amira (Faculty of Business and Management, 2019)
This study was conducted to study the impact of the positive relationship of political skills towards organizational commitment among Petroliam Nasional Berhad employees. It used a survey questionnaire to obtain information from the employees through judgement method. The theoretical framework of this study was based on the organizational commitment and political skills theories throughout various studies of different author. This findings of the study shows that only social astuteness and apparent sincerity did not have positive relationship with organizational commitment while interpersonal influence and networking ability do have positive relationship with organizational commitment.